DETERMINATION, PAR DES METHODES AB INITIO ET DFT, DES SITES ET ENERGIES DE PROTONATION D’UNE SERIE DE MOLECULES D’IMIDAZOPYRIDINYL-CHALCONES SUBSTITUEES - Thomas, Affi Sopi; Nahossé, Ziao; Kafoumba, Bamba (European Scientific Journal, ESJ, 2015)
Imidazopyridinyl-chalcones (IPC) and their derivatives possess a wide range of biological properties. In this work, we are interested in seven of these compounds. Each of them is formed of an IPC nuclei that comprises three heteroatoms and an aryl substituent. Our work aims to determine the major site of protonation on the IPC nuclei, by studying the process of the protonation reaction on each heteroatom. Therefore, quantum mechanical calculations have been used at both HF/6-311+G(d,p) and B3LYP/6- 311+G(d,p) levels to determine proton affinity (PA) and gas phase basicity (GB) for each of the seven IPC and each of heteroatom. The choice of Hartree-Fock and DFT/B3LYP methods leads to less heavy calculations as well as we obtain good results for compouds as IPC. These methods, combined with split-valence basis set, wich takes into account diffuse functions on heavy atoms, are very important, as we aim to study intermolecular interactions. It follows up, after all calculations, that the sp2 nitrogen atom was admitted to be the major site of protonation in gas phase middle. Furthermore, it has been pointed out that the proton affinity strength depends on the aryl substituent group. In addition, the electro attractor aryl group was assumed to toughen the proton affinity of the IPC nuclei.